Fire Regime, Climate, and Vegetation in the Sierras de Córdoba, Argentina - Argañaraz, Juan Pablo (2015)
Wildfires are a primary disturbance in the Sierras de Córdoba, Argentina, with approximately 2 152 000 ha burned between 1993 and 2012. However, little is known about the spatial and temporal patterns of fires and their relationship with climate and vegetation in this area. Such information is of great value for fire risk assessment and the development of strategies for fire management. Our main objective was to analyze fire activity in four sierran ranges, assessing which weather and climate conditions were mostly related to fire activity, and which land cover types were mostly burned. We used a fire database of mid-high spatial resolution and a land cover map derived from Landsat imagery. Fire regimes were different among the different sierran ranges. The Sierras Chicas range was the most affected by fires, with the largest number of fire events, burned area, and fire frequency. Although large fires represented 3% to 5% of fire events, they accounted for 60% to 86% of total burned area in different sierran ranges. Sierras of lower elevation had a winter seasonality of fires, while sierras of higher elevation had a winter-spring or spring fire seasonality. The number of fire events was positively correlated with preceding periods that were wetter than normal, while the burned area was mainly associated with midterm weather conditions. Fires occurred mainly in grasslands and shrublands, but the area of burned forests was important, too. Our results will be useful to determine the times and conditions in which fire risk is highest, and also to identify where preventive efforts should be focused.